SOME ISSUES OF PROFESSIONAL EDUCATION OF STUDENTS - AMELINA, Svitlana (Trends in education, 2012)
The article is dedicated to the issue of professional education of students. The professional competence as an element of professional formation is defined.
Keywords: professional education; professional competence; higher educational institutions.